2021
DOI: 10.1016/j.jinf.2021.04.029
|View full text |Cite
|
Sign up to set email alerts
|

Household clustering of SARS-CoV-2 variant of concern B.1.1.7 (VOC-202012–01) in England

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 4 publications
3
18
0
Order By: Relevance
“…Cases who were able to effectively isolate may have avoided transmitting the infection to other household members, as previous studies have suggested [29], but were more likely to be re-exposed to SARS-CoV-2 at a later point. Increased odds of quarantine were also observed as the year progressed, supporting earlier ndings of increased transmissibility of the Alpha variant, rst detected in the UK in November 2020 and the predominant lineage by February 2021 [31,32].…”
Section: Discussionsupporting
confidence: 77%
“…Cases who were able to effectively isolate may have avoided transmitting the infection to other household members, as previous studies have suggested [29], but were more likely to be re-exposed to SARS-CoV-2 at a later point. Increased odds of quarantine were also observed as the year progressed, supporting earlier ndings of increased transmissibility of the Alpha variant, rst detected in the UK in November 2020 and the predominant lineage by February 2021 [31,32].…”
Section: Discussionsupporting
confidence: 77%
“…Previous emerging SARS-CoV-2 variants, Alpha and Delta, resulted in surges in incidence in England, with increased household clustering observed for both these variants. 9-11 In contrast, Beta and Gamma variants had lesser impact on case numbers after their emergence. 8…”
Section: Introductionmentioning
confidence: 93%
“…8 Previous emerging SARS-CoV-2 variants, Alpha and Delta, resulted in surges in incidence in England, with increased household clustering observed for both these variants. [9][10][11] In contrast, Beta and Gamma variants had lesser impact on case numbers after their emergence. 8 We applied two different methods (secondary attack rate estimates, household clustering) to assess the transmissibility of the emerging SARS-CoV-2 Omicron variant compared to the Delta variant at a time when both variants were circulating in England.…”
Section: Introductionmentioning
confidence: 94%
“…A total of 37 studies reporting on public health measures in relation to VOC were included after screening. The majority of included studies reported on the Alpha VOC (n=32) 24–54. The majority of studies were conducted in Europe (n=12),24 29 30 34 35 39 40 44 47 51 53 55 followed by the UK (n=9),26 28 32 33 36 42 45 50 56 USA (n=9),25 37 38 41 43 48 49 54 57 Brazil (n=3),58–60 Canada (n=1),31 South Africa (n=1),27 Israel (n=1)46 and Japan (n=1)52 (figure 2).…”
Section: Resultsmentioning
confidence: 99%
“…The majority of included studies reported on the Alpha VOC (n=32) 24–54. The majority of studies were conducted in Europe (n=12),24 29 30 34 35 39 40 44 47 51 53 55 followed by the UK (n=9),26 28 32 33 36 42 45 50 56 USA (n=9),25 37 38 41 43 48 49 54 57 Brazil (n=3),58–60 Canada (n=1),31 South Africa (n=1),27 Israel (n=1)46 and Japan (n=1)52 (figure 2). Additional details of each study can be found in the online supplemental material 2.…”
Section: Resultsmentioning
confidence: 99%